Green homes : new ideas for sustainable living - Costa Duran, Sergi; Hosey, Lance (New York : HarperCollins Publishers, 2007)
GREEN HOMES presents the latest innovations in sustainable architecture in design. After an introductory interview with an international specialist in green building, the book features 35 projects, including houses, apartments, offices, sports facilities, and factories. It explores various aspects of green design, from its ecological and economical benefits, to factors considered when choosing materials: how much energy went into manufacturing the product, whether it is long lasting, and whether it can be recycled or safely disposed of as it breaks down over time. Specific topics covered include climate regulation, drainage systems, and regional planning. Each project contains photographs, floor plans and detailed drawings that illustrate certain sustainable features, revealing reveal how much the parameters of ecological design have expanded in just a few short years